Florapedia : a brief compendium of floral lore - Gracie, Carol (Princeton University Press, 2021)
"This book is an engaging and informative compendium of flower facts. Similar in a nature to Lawrence Millman's Fungipedia, the book brings together a wide range of interesting facts and stories-ranging from the historical to the scientific to the whimsical. The book has roughly 100 entries, beginning with achlorophyllous flowers that feed on the roots of a host plant, and ending with zygomorphic flowers, that pose an interesting puzzle for pollinators. In the entries in-between, readers will explore with John and William Bartram, smell the rotting corpse flower, learn about the miniature ecosystems entangled in Spanish moss, and much more. Similar to Fungipedia, the book is intended for a general audience, but thanks to Gracie's depth and breadth of knowledge, and her artful prose, it will also appeal to seasoned flower enthusiasts. The entries are accompanied by approximately 50 line drawings from Amy Jean Porter"--